Lexico-semantic features of ecological terms connected with water - Z.Djurabaeva (Indonesian Journal of Innovation Studies, 2019)
The article deals with the lexical units and their lexical-semantic features associated with the concept "water". On this case, research has been mentioned on different points of the lexico-semantic features of ecological terms connected with water. It concludes with the outcomes and shortcomings as the whole.